The effect of jumps in the crude oil market on the sovereign risks of major oil exporters - Elie Bouri (Risks, 2019)
We study the jump behaviour in the sovereign risks of major oil-exporting countries and examine whether it is affected by jumps in the price and volatility of crude oil. Data used are daily from 14 February 2011, to 31 July 2019. We detect the presence of jumps in many oil exporters and find evidence of less frequent jumps in the crude oil market. The jumps in sovereign risks of oil-exporters are significantly affected by oil volatility jumps, not by oil price jumps. These findings suggest that the sovereign risks of oil-exporters are affected by abrupt movements in oil implied volatility, which points to a contagion effect. The findings are useful not only for refining the prediction of the sovereign risks of oil-exporters but also in reducing the potential effect of price discontinuity of sovereign risks on public finances sustainability and financial health.
Keywords: C22; G10; 330; crude oil; jumps; oil implied volatility; sovereign risks of oil-exporters